Short-term HIIT impacts HDL function differently in lean, obese, and diabetic subjects - Zhu, Lin; An, Julia; Luu, Thao; Reyna, Sara M.; Tantiwong, Puntip; Sriwijitkamol, Apiradee; Musi, Nicolas; Stafford, John M. (Frontiers in Physiology, 2024)
High density lipoproteins (HDL) exert cardiovascular protection in part through their antioxidant capacity and cholesterol efflux function. Effects of exercise training on HDL function are yet to be well established, while impact on triacylglycerol (TG)-lowering has been often reported. We previously showed that a short-term high-intensity interval training (HIIT) program improves insulin sensitivity but does not inhibit inflammatory pathways in immune cells in insulin-resistant subjects.The purpose of this study is to evaluate HDL function along with changes of lipoproteins after the short-term HIIT program in lean, obese nondiabetic, and obese type 2 diabetic (T2DM) subjects. All individuals underwent an HIIT for 15 days. Blood lipid profile and HDL function were analyzed before and after the HIIT program. Along with improvements in blood lipid profile in obese and T2DM subjects, the HIIT program affected circulating apolipoprotein amounts differently. The HIIT program increased HDL-cholesterol levels and improved the cholesterol efflux capacity only in lean subjects.Furthermore, the HIIT program improved the antioxidant capacity of HDL in all subjects. Data from multiple logistic regression analysis showed that changes in HDL antioxidant capacity was inversely associated with changes in atherogenic lipids and changes in HDL-TG content. We show that a shortterm HIIT program improves aspects of HDL function depending on metabolic contexts, which correlates with improvements in blood lipid profile. Our results demonstrate that TG content in HDL particles may play a negative role in the anti-atherogenic function of HDL.